CHAPTER 13: Coherent Control of Cold Collisions - Koch, Christiane P. (Royal Society of Chemistry, 2018)
Coherent control exploits quantum pathway interference to steer the dynamics of a quantum system in the desired way. The dynamical interferences can be introduced in various ways. In this chapter the overall concept of coherent control together with different realizations is introduced, and the difficulty of coherently controlling cold collisions is analyzed in depth. As an example, photoassociation, i.e., the formation of a chemical bond by an external field, is considered. Prospects for controlling cold collisions beyond photoassociation are discussed.
CRIS-Team Scopus Importer:2023-04-20